2021
DOI: 10.1029/2021jc017792
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Summer Marine Heatwaves in the South China Sea

Abstract: Anthropogenic climate change mainly results from the continuous emission of greenhouse gases that induce the energy imbalance in Earth's climate system (IPCC, 2014;Von Schuckmann et al., 2020). Over 90% of the excess heat from the greenhouse effect is absorbed by the oceans, and 52% is absorbed by the upper water layers within 700 m depth, leading to a temperature increase in the upper ocean (Cheng et al., 2019). Marine heatwaves (MHWs), a discrete period of anomalously warm seawater exceeding seasonal variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 82 publications
2
82
0
Order By: Relevance
“…The close correlation between the local mean SST and MHW days and frequency suggest that the background monthly mean atmospheric and oceanic conditions caused by climate change are important for the formation of MHWs. The heat budget analyses conducted by, for example, Li and Wang [22] and Saranya et al [24] are required to fully unravel the physical processes of the BOB MHWs occurring at different locations and during different seasons. The linear trend caused by global warming has not fully emerged for the warm season MHWs in the BOB in recent decades, but once the background temperatures significantly changes, it would fuel more powerful and devastating MHWs.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…The close correlation between the local mean SST and MHW days and frequency suggest that the background monthly mean atmospheric and oceanic conditions caused by climate change are important for the formation of MHWs. The heat budget analyses conducted by, for example, Li and Wang [22] and Saranya et al [24] are required to fully unravel the physical processes of the BOB MHWs occurring at different locations and during different seasons. The linear trend caused by global warming has not fully emerged for the warm season MHWs in the BOB in recent decades, but once the background temperatures significantly changes, it would fuel more powerful and devastating MHWs.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Climate modes play an important role in modulating the variability of MHWs, but the dominant modes substantially vary across regions. Generally, MHWs are closely associated with the El Niño and Southern Oscillation (ENSO), the Indian Ocean basin mode (IOB) and dipole mode (IOD) and the Pacific Decadal Oscillation (PDO) in Indo-Pacific regions [19][20][21][22][23][24][25][26]. The North Atlantic Oscillation (NAO) is also shown to be connected with the formation of Indian Ocean MHWs [13,24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, summer MHWs in the SCS have been reported (Yao and Wang, 2021). Under the influence of intensification of the western North Pacific subtropical high, upwelling in the midwestern SCS weakens and then causes basin-wide severe summer MHWs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies confirmed that ocean temperature plays a vital role in the ecosystems, dynamics and thermodynamics of the SCS. For example, ocean temperature variability can significantly influence the occurrence of marine heatwaves in the SCS [18]. In addition, ocean temperature can also play a role in the processes of air-sea interactions in the SCS, which can exert noticeable impacts on the East Asian climate [19].…”
Section: Introductionmentioning
confidence: 99%